2018
DOI: 10.1002/apj.2211
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics and kinetics of synthesized anionic surfactant and polymeric surfactant on sand surface for application in enhanced oil recovery

Abstract: The adsorption behaviour of aqueous solutions of anionic surfactant and polymeric surfactant derived from Jatropha oil onto sand surface was investigated in connection of their application in enhanced oil recovery. The loss of surfactant by adsorption on reservoir rock must be premeditated for proper design of injected surfactant slugs in a chemical enhanced oil recovery. The sand particles used in the present study as representative of reservoir rock were characterized by Fourier transform infrared and energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The absorption band around 2,920, 2292, and 2236 cm −1 in the three spectrograms shown in Figure 10 depict the C-H symmetric vibration of the saturated hydrocarbons and O-H band due to stretching vibration at 3,435 cm −1 . C¼O stretching peaks appeared between 1,627 and 1,870 cm −1 , which confirms the presence of carbonyl components like acids and aliphatic esters in the sand particles (Saxena, Kumar, & Mandal, 2018).…”
Section: Figure 9 Barotac Viejo Landslide Prone Area Ftir Analysissupporting
confidence: 52%
“…The absorption band around 2,920, 2292, and 2236 cm −1 in the three spectrograms shown in Figure 10 depict the C-H symmetric vibration of the saturated hydrocarbons and O-H band due to stretching vibration at 3,435 cm −1 . C¼O stretching peaks appeared between 1,627 and 1,870 cm −1 , which confirms the presence of carbonyl components like acids and aliphatic esters in the sand particles (Saxena, Kumar, & Mandal, 2018).…”
Section: Figure 9 Barotac Viejo Landslide Prone Area Ftir Analysissupporting
confidence: 52%
“…The assumption of the Temkin model was that during the adsorption process the heat of adsorption decreases linearly and is not a function of logarithmic ( Saxena et al, 2018 ). The Temkin model is expressed as the Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The Temkin model is expressed as the Eq. 4 ( Ahmadi and Shadizadeh 2015 ; Saxena et al, 2018 ), where q e is the quantity of the surfactant adsorption at the equilibrium per unit mass of calcium carbonate (mg/g), Ce is the surfactant equilibrium concentration in solution (mg/L), B is the Temkin constant, K T is the equilibrium binding (L/mg), respectively. …”
Section: Methodsmentioning
confidence: 99%
“…Owing to the importance of surfactant adsorption-desorption properties, studies have been where the adsorption was researched under conditions that resemble those of Mexican reservoirs (Flores et al, 2011;Toledo-Piña et al, 2014). Studies under high salinity conditions, over limestone, over-carbonated surfaces, and sandstones are also available (Barati et al, 2016;Budhathoki et al, 2016;Chen et al, 2017;Han et al, 2013;Saxena et al, 2018;Wang et al, 2015). Massarweh and Abushaikha (2020) reviewed the use of surfactants in EOR in 2020, they found that the surfactants have successfully increased the oil recovery through interfacial tension reduction, wettability alteration, foam generation, and emulsification.…”
Section: Introductionmentioning
confidence: 99%